Oligometastasis to testis in prostate cancer: Role of gallium-68 prostate-specific membrane antigen positron-emission tomography computed tomography - Manoj Gupta; Partha Choudhury; Sudhir Rawal; Amitabh Singh (World Journal of Nuclear Medicine)
Accurate staging and restaging with early detection of recurrent site is the key for planning treatment in patients of prostate cancer. Recently, gallium-68 prostate-specific membrane antigen positron-emission tomography computed tomography (68Ga-PSMA PET/CT) has emerged as a better tool for this. Few uncommon sites of early metastasis can also be identified in addition to the other common sites. Herein, we present three cases of early metastasis to testis in prostate cancer identified on 68Ga-PSMA PET/CT scan.